2020
DOI: 10.22161/ijeab.56.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of followed production procedures on the physicochemical properties of labneh anbaris

Abstract: The aim of this study is to assess the different recorded processing attributes on physicochemical properties of anbaris and comparing them to commercially produced labneh done from pasteurized cow and goat milk. Comparing the industrially produced IP-anbaris with labneh industrially produced using cows and goat milk showed that the cow-labneh possessed significantly lower total-solids, titratable acidity, salt, ash, fat and protein content while having significantly higher pH and moisture content. As for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…From that point on, moisture decreased steadily. The variation trend of moisture content understandably influenced the trends of protein and fat variation that concentrated over time to reach, in the end product, values in the range of what is described elsewhere for Anbaris (Dimassi et al ., 2020a, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From that point on, moisture decreased steadily. The variation trend of moisture content understandably influenced the trends of protein and fat variation that concentrated over time to reach, in the end product, values in the range of what is described elsewhere for Anbaris (Dimassi et al ., 2020a, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…These factors, associated with the microbial consortium species nature and equilibrium, are thought to contribute to raw milk products safety (Montel et al ., 2014; Arias-Roth et al ., 2022). No reports are available to know if food borne illnesses are associated with the consumption of Anbaris, but the product is reported as most frequently exempt of pathogens (Dimassi et al ., 2020a, 2020b). Our results also showed that major pathogens usually found in milk were absent from our final fresh product.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation